DETERMINATION OF SPRAY ANGLE AND FLOW UNIFORMITY OF SPRAY NOZZLES WITH IMAGE PROCESSING OPERATIONS - N. Çetin; C. Sağlam; B. Demir (Journal of Animal and Plant Sciences, 2019)
This study was conducted to determine the spray angle and flow uniformity of different hydraulic spray nozzles at different spray pressures with the aid of image processing operations. Spray images were captured with a digital camera to determine spray angles and spray patterns. Captured images were transferred to computer environment and analyzed with different image processing software. The spray angle at 3 bar pressure was measured as 107.2º for anti-drift nozzles, as 105.6º for air-injection nozzles, as 69.9º for ST 80 flat-fan nozzles, as 84.0º for ST 90 flat-fan nozzles, as 103.2º for ST 110 flat-fan nozzles and as 54.2° for hollow-cone Ø1.0 mm nozzles. Cone angle at 3 bar pressure was measured as 106.7º for anti-drift nozzles, as 103.9º for air-injection nozzles, as 75.1º for ST 80 flat-fan nozzles, as 86.4º for ST 90 flat-fan nozzles, as 105.2º for ST 110 flat-fan nozzles and as 46.4º for hollow-cone Ø1.0 mm nozzles. Spray pattern obtained with the image processing method was identical with the flow uniformity obtained with line-profile method. It was concluded that spray pressures had significant effects on spray angles (p ≤0.05) of all nozzles.
Keywords: Cone angle; image processing; pressure; spray angle; spray pattern